In Silico Neuroproteomic Profiling of Chicken Brain Development Reveals Stage-Specific Molecular Signatures and Functional Pathways - Swaroop Murikipudi, Naveen; Injarapu, Vasantha; Kantepudi, Archana (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Brain development in vertebrates is a highly coordinated process involving the temporal and spatial expression of proteins that govern  neural induction, patterning, differentiation, and maturation. In the chicken model, SDS-PAGE profiling across developmental stages - from  embryonic day 0 to adulthood - has revealed stage-specific protein bands indicative of dynamic proteomic shifts. However, the functional  identity and biological relevance of these proteins remain underexplored. In this study, we employed an in silico neuroproteomic  approach to annotate and analyze these developmentally regulated proteins. Using tools such as BLAST, STRING, PANTHER, and DAVID,  we mapped each protein to its respective biological processes, cellular components, and molecular functions. Key proteins such as  FGF2, amyloid precursor protein (APP), myelin basic protein (MBP), and β-catenin exhibited distinct expression patterns correlating with  critical neurodevelopmental events, including axoneogenesis, synaptogenesis, and myelination. Protein-protein interaction networks  revealed hubs central to neural signaling, structural organization, and brain maturation. Pathway enrichment analysis further highlighted  involvement in Wnt signaling, neurotrophin signaling, and myelin sheath formation. This integrative analysis provides a systems-level  view of chicken brain development, underscoring conserved and stage-specific molecular pathways. Our findings offer valuable insights  for neurobiology and open new avenues for translational research in poultry production.
Keywords: Chicken brain; Embryogenesis; Gallus gallus; In-silico proteomics; Neurodevelopment; Pathway analysis; Protein interaction